Pengaruh Indepedensi, Kompetensi dan Professional Skepticism terhadap Kemampuan Auditor Internal Pemerintah dalam Mendeteksi Fraud - Salsabila, Ananda; Afriyenti, Mayar; Honesty, Helga Nuri (Universitas Negeri Padang, 2023)
The purpose of this study was to determine the effect of independency, competency, and professional skepticism toward government internal auditor's ability to detect fraud The population in the survey is to auditor who works in Payakumbuh City Inspectorate (Inspektorat Kota Payakumbuh), Fifty Cities Regency Inspectorate (Inspektorat Kabupaten Lima Puluh Kota), and Bukittinggi City Inspectorate (Inspektorat Kota Bukittinggi) the research design in this study is a quantitative approach using primary data Primary data was obtained by total sampling by from 60 respondents the results of study are independency, competency, and professional skepticism have significantly and positively effect toward government internal auditor's ability to detect fraud.